Histological and Serological Epidemiology of Hepatitis Delta Virus Coinfection among Patients with Chronic Active Hepatitis B Virus in Razavi Khorasan Province, Northeastern Iran - Payam SHARIFAN; Sakineh AMOUEIAN (Tehran University of Medical Sciences, 2018)
Background: Hepatitis delta virus (HDV), as well as hepatitis B virus (HBV), are regarded as one of the main public health issues in developing countries. This retrospective study described histological and serological features of HDV coinfection patients with chronic active HBV in Northeastern Iran. Methods: The frequency of HDV seropositivity and its impact on serum liver enzyme levels and pathological features were investigated by reviewing clinical and laboratory data. This study contained chronic active HBV-infected patients having admitted the department during 2009 and 2014. Results: The rate of HDV coinfection in chronic active carriers was 21.84%, with a male predominance. HDV seropositive carriers showed significantly higher concentrations of liver enzyme than chronic active HBV monoinfection. Moreover, there was a strong association between degrees of inflammation with HDV-positive patients' enzyme levels. Conclusion: The HDV seroprevalence in northeastern Iran was higher than that reported from elsewhere in Iran while comparable to some regions in Middle East, which, in turn, requires more comprehensive tools for diagnosing and screening the blood.